The Association of Serum Uric Acid with Beta-Cell Function and Insulin Resistance in Nondiabetic Individuals: A Cross-Sectional Study - Yu P (Dove Medical Press, 2021)
Peng Yu,1,2 Li Huang,1,2 Zhihan Wang,1,2 Xiaoyu Meng,1,2 Xuefeng Yu1,2 1Department of Internal Medicine, Tongji Hospital, Huazhong University of Science and Technology, Wuhan, Hubei, 430030, People’s Republic of China; 2Branch of National Clinical Research Center for Metabolic Diseases, Hubei, ChinaCorrespondence: Xuefeng Yu Tel/Fax +8602783663331Email xfyu188@163.comPurpose: Higher serum levels of uric acid (SUA) are associated with an increased risk of developing type 2 diabetes. Meanwhile, insulin resistance and beta-cell dysfunction are critical factors that mediate the progression from normal glucose tolerance to impaired fasting glucose (IFG) and type 2 diabetes. We aimed to investigate the association between SUA levels and insulin resistance and beta-cell dysfunction in individuals without diabetes, thus explicating the role of uric acid in the early stage of the natural history of type 2 diabetes.Patients and Methods: We used cross-sectional data from the China Health and Nutrition Survey to examine the association. Insulin resistance and beta-cell dysfunction were estimated using the homeostasis model assessment of insulin resistance (HOMA-IR) index and homeostasis model assessment of beta-cell function (HOMA-beta) index, respectively. The associations were analyzed by using partial correlation analysis and multivariate logistic regressionl analysis.Results: SUA levels were positively associated with fasting glucose, fasting insulin, HOMA-IR in the total population. After adjustment for age, drinking, smoking, living area, daily dietary nutrient intake, body mass index (BMI), estimated glomerular filtration rate (eGFR), hypertension, and dyslipidemia, compared with participants in the lowest quartile of SUA, the adjusted odds ratios for the fourth quartiles were 1.56(1.09-2.24) for IFG, 1.51(1.27-1.78) for insulin resistance, and 1.06(0.88-1.27) for beta-cell dysfunction. In the subgroup analysis, no interactions were found between serum uric acid and age, drinking status, smoking status, BMI, hypertension, or dyslipidemia (all p for interaction> 0.05).Conclusion: In nondiabetic individuals, SUA levels are independently associated with IFG and insulin resistance, while no significant association exists between SUA and beta-cell dysfunction.Keywords: uric acid, beta-cell function, insulin resistance, nondiabetic